The preservation the historical heritage of the October XXXI academic center School of Nursing, University of São Paulo - Jaqueline de Andrade Oliveira; Genival Fernandes de Freitas (Universidad de Alicante, 2012)
Preservation of documents is justified by the importance of the existing collection of documents in October XXXI Academic Center of the School of Nursing of USP in order to provide for the organization and the access to future researchers interested in the history of nursing, as well as safeguard the collective memory of that profession. This study aimed to sanitize, organize and prepare an inventory of documentation of October XXXI Academic Center of the School of Nursing. Methodologically, documents were submitted to the diplomatic and typological analyzes and then were cleaned and organized in terms of archival, according to thematic affinity. For this purpose, we developed spreadsheets in Excel. The results revealed a large mass of documents, which was organized by thematic affinity, yielding a total of 9 subjects, totaling the amount of 1028 documents: National Union of Students -UNE (134), State Union of Students -UEE (131); Incoming Correspondence general (76); Correspondence Received - USP (140); Entities and Institutions Nursing student (60); Correspondence issued (229); Organisation Finances (150); Sparse Documentation (99) and Iconographic and Press material (9). The present study allowed a fresh look at the value of the document as a source of research and re-signified the social locus of collective memory.